2005
DOI: 10.1051/ject/200537009
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Acute Preoperative Plateletpheresis, Cell Salvage, and Aprotinin Minimizes Blood Loss and Requirement During Cardiac Surgery

Abstract: Acute preoperative plateletpheresis (APP), cell salvage (CS) technique, and the use of aprotinin have been individually reported to be effective in reducing blood loss and blood component transfusion while improving hematological profiles in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). In this prospective randomized clinical study, the efficacy of these combined approaches on reducing blood loss and transfusion requirements was evaluated. Seventy patients undergoing primary coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Then in 1987, Ferrari et al 27 performed perioperative plasmapheresis to collect aPRP and demonstrated a reduction in blood loss and the need for allogeneic blood transfusion. Since then, APP has been widely used in cardiovascular surgery because it sets aside a subset of the patient’s own platelets from the circulation during surgery and prevents exposure of that platelet subset to the CPB circuit, decreasing the risk of global platelet dysfunction 8 9 28. The Society of Thoracic Surgeons and the Society of Cardiovascular Anesthesiologists recommended in 201129 that APP may be a reasonable approach to support blood conservation strategies in high-risk patients if an adequate yield can be reliably obtained (class IIa, level of evidence A).…”
Section: Discussionmentioning
confidence: 99%
“…Then in 1987, Ferrari et al 27 performed perioperative plasmapheresis to collect aPRP and demonstrated a reduction in blood loss and the need for allogeneic blood transfusion. Since then, APP has been widely used in cardiovascular surgery because it sets aside a subset of the patient’s own platelets from the circulation during surgery and prevents exposure of that platelet subset to the CPB circuit, decreasing the risk of global platelet dysfunction 8 9 28. The Society of Thoracic Surgeons and the Society of Cardiovascular Anesthesiologists recommended in 201129 that APP may be a reasonable approach to support blood conservation strategies in high-risk patients if an adequate yield can be reliably obtained (class IIa, level of evidence A).…”
Section: Discussionmentioning
confidence: 99%